3EIBS: A constellation of fungus gnats (Diptera: Keroplatidae and Mycetophilidae) from caves of Parc Natural dels Ports, Tarragona, western Catalonia - J. Mederos Lopez; P. J. Chandler (Arxius de Miscel-lània Zoològica)
A preliminary approximation of the fungus gnat fauna (Diptera: Keroplatidae and Mycetophilidae) is presented, captured in caves of the Parc Natural dels Ports (Tarragona, Catalonia) following surveys conducted in the massif in 2012. We report a total of 11 species from ten prospected caves and provide data on the biology and images where possible. Exechiopsis coremura (Edwards) stands out due to few previous records of this species in the Iberian peninsula.